Prognosis value of Forrester's classification in advanced heart failure patients awaiting heart transplantation. (7th July 2022) - Baudry, Guillaume; Coutance, Guillaume; Dorent, Richard; Bauer, Fabrice; Blanchart, Katrien; Boignard, Aude; Chabanne, Céline; Delmas, Clément; D'Ostrevy, Nicolas; Epailly, Eric; Gariboldi, Vlad; Gaudard, Philippe; et al.
Abstract: Aims: The value of Forrester's perfusion/congestion profiles assessed by invasive catheter evaluation in non‐inotrope advanced heart failure patients listed for heart transplant (HT) is unclear. We aimed to assess the value of haemodynamic evaluation according to Forrester's profiles to predict events on the HT waitlist. Methods and results: All non‐inotrope patients ( n  = 837, 79% ambulatory at listing) registered on the French national HT waiting list between 1 January 2013 and 31 December 2019 with right heart catheterization (RHC) were included. The primary outcome was a combined criteria of waitlist death, delisting for aggravation, urgent HT or left ventricular assist device implantation. Secondary outcome was waitlist death. The 'warm‐dry', 'cold‐dry', 'warm‐wet', and 'cold‐wet' profiles represented 27%, 18%, 27%, and 28% of patients, respectively. At 12 months, the respective rates of primary outcome were 15%, 17%, 25%, and 29% ( P  = 0.008). Taking the 'warm‐dry' category as reference, a significant increase in the risk of primary outcome was observed only in the 'wet' categories, irrespectively of 'warm/cold' status: hazard ratios, 1.50; 1.06–2.13; P  = 0.024 in 'warm‐wet' and 1.77; 1. 25–2.49; P  = 0.001 in 'cold‐wet'. Conclusions: Haemodynamic assessment of advanced HF patients using perfusion/congestion profiles predicts the risk of the combine endpoint of waitlist death, delisting for aggravation, urgent heart transplantation, or left ventricular assist device implantation. 'Wet' patients had the worst prognosis, independently of perfusion status, thus placing special emphasis on the cardinal prominence of persistent congestion in advanced HF.